Adsorption behavior of cadmium ions onto phosphoric acid-impregnated microwave-induced mesoporous activated carbon. (December 2016) - Tan, I.A.W.; Chan, J.C.; Hameed, B.H.; Lim, L.L.P.
Graphical abstract: Highlights: Mesoporous activated carbon was derived from oil palm shell for cadmium removal. Phosphoric acid impregnation followed by microwave irradiation was applied. Activated carbon showed high BET surface area of 854.42 m 2 /g. Acidic pH was more favourable for cadmium adsorption. Activated carbon exhibited high cadmium adsorption of 227.27 mg/g at 30 °C. Abstract: This study investigated the potential of mesoporous activated carbon derived from oil palm shell using phosphoric acid (H3 PO4 ) impregnation followed by microwave-induced irradiation, for adsorption of cadmium from aqueous solution. This study investigated the effects of H3 PO4 impregnation ratio (1:1, 1:2 and 1:3 w/w) and microwave irradiation time (5 and 8 min) on the characteristics of the synthesized activated carbon, encompassing the textural, morphological, proximate and chemical properties. Batch adsorption studies were conducted for the activated carbon to determine the effects of contact time, initial cadmium concentration (20–200 mg/L) and solution pH (2–10) on the cadmium ions uptake at 30 °C. The synthesis process resulted in the development of pores, with average diameter of 2.22 nm, on the surface of the oil palm shell, which contributed to the relatively large BET surface area and total pore volume of 854.42 m 2 /g and 0.74 cm 3 /g, respectively. Batch adsorption studies showed that the adsorption of cadmium increased with increasing concentration and was more favourable at acidic pH, achieving up to 99% removal. The adsorption of cadmium on the activated carbon was of chemisorption and governed by external mass transport. The maximum monolayer adsorption capacity of 227.27 mg/g showed the potential of the proposed synthesis method for deriving mesoporous oil palm shell-based activated carbon for removing cadmium from aqueous solutions. The saving in terms of the reduction of activation time and energy usage shall make the production of activated carbon from agricultural biomass to be more environmental friendly and sustainable for wastewater treatment.